The effects of genotype and/or environment on the phenotypic expressions of mandibular gland signals in honeybees (Apis mellifera) - Noach-Pienaar, Lee-Ann (Stellenbosch : Stellenbosch University, 2011)
Thesis (PhD (Botany and Zoology))--Stellenbosch University, 2011.